2020
DOI: 10.1590/pboci.2020.121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Resin Coating Material on the Microleakage of Class V Restorations With or Without Post-Operative Bleaching

Abstract: To evaluate the effect of a resin coating material on the microleakage of Class V composite resin restorations with and without post-operative bleaching. Material and Methods: Eighty class V cavities (3×3×1.5 mm) were prepared and filled with Z250 XT composite resin in the buccal and lingual surfaces of 40 sound human molars. Then the samples were randomly divided into 4 groups (n=20) and treated as follows: Group A: applying a resin coating (G-Coat Plus) on the restoration, then bleaching with 40% hydrogen pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Therefore, it is easily affected by the chemicals in bleaching agents. Hajilou et al 18 investigated the effect of 40% hydrogen peroxide bleaching on the microleakage of composite resin restorations, reporting that bleaching after restoration increases the microleakage, with significantly greater microleakage in gingival margins.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is easily affected by the chemicals in bleaching agents. Hajilou et al 18 investigated the effect of 40% hydrogen peroxide bleaching on the microleakage of composite resin restorations, reporting that bleaching after restoration increases the microleakage, with significantly greater microleakage in gingival margins.…”
Section: Discussionmentioning
confidence: 99%
“…A protective coating either with light polymerized low viscosity unfilled resin adhesives or G-coat plus is compulsory for all the glass ionomer materials to enhance the wear resistance [23,24]. Conversely, some studies reported no difference in surface roughness values in coated and uncoated specimens [14].…”
Section: Discussionmentioning
confidence: 99%
“…3,5,6 Microleakage is clinically associated with staining around the restoration margins, postoperative sensitivity, secondary caries, pulpal pathology, lower bond strength, and the subsequent partial or total failure of the restoration. 7 Since restoration durability highly depends on the integrity and longevity of the marginal seal, various methods and compensatory mechanisms have been tried to decrease the marginal gap at the tooth-restoration interface. 8 As a novel recommended technique, surface coating materials can be applied on the finished restoration cavosurface margins to penetrate the marginal gaps and structural microdefects by capillary action, thereby enhancing the marginal seal of esthetic restorative materials.…”
Section: Introductionmentioning
confidence: 99%
“…3 Coating materials are said to bond strongly with enamel, composite, dentin, ionomer, glass and resin-modified glass ionomers. 7 G-Coat Plus is a methyl methacrylate-based photopolymerized resin-based coating material with low viscosity that is filled with nanofillers for better wear resistance. 9 In permanent teeth, coating restores the marginal integrity and reduces the gingival microleakage in Class V restorations at enamel and dentin margins.…”
Section: Introductionmentioning
confidence: 99%